2013
DOI: 10.2174/1874285801307010059
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Efflux Pumps in Staphylococcus aureus: an Update

Abstract: The emergence of infections caused by multi- or pan-resistant bacteria in the hospital or in the community settings is an increasing health concern. Albeit there is no single resistance mechanism behind multiresistance, multidrug efflux pumps, proteins that cells use to detoxify from noxious compounds, seem to play a key role in the emergence of these multidrug resistant (MDR) bacteria. During the last decades, experimental data has established their contribution to low level resistance to antimicrobials in ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
304
4
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(318 citation statements)
references
References 148 publications
(218 reference statements)
6
304
4
4
Order By: Relevance
“…The results of Hauschild demonestrate that all amino acid alteration cause fluoroquinolone resistance in gyrA were related to the Ser84->Leu and in one sample Glu88->Asp was observed (Hauschild et al, 2012). In the study of Santos Costa reported that nearly all gyrA mutations related to fluoroquinolone resistance in Staphylococcus aures was Ser84->Leu and in 3 isolates Glu88->Lys was identified (Costa et al, 2013). In the study of Rasha Ser84->Leu, two silent mutations in Ile86 and Leu103, Glu88->Lys, Gly106->Asp, Ser112->Arg in GyrA was reported (Hashem et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Hauschild demonestrate that all amino acid alteration cause fluoroquinolone resistance in gyrA were related to the Ser84->Leu and in one sample Glu88->Asp was observed (Hauschild et al, 2012). In the study of Santos Costa reported that nearly all gyrA mutations related to fluoroquinolone resistance in Staphylococcus aures was Ser84->Leu and in 3 isolates Glu88->Lys was identified (Costa et al, 2013). In the study of Rasha Ser84->Leu, two silent mutations in Ile86 and Leu103, Glu88->Lys, Gly106->Asp, Ser112->Arg in GyrA was reported (Hashem et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, shortly after their introduction into the clinical practice, the first bacteria showing antibioticresistant were described. Since then the development of new antibiotics have been attend by the constant increase of antibiotic-resistant bacterial strains and different mechanisms used by bacteria to repress the fatal effect of these compounds (Costa et al, 2013). In the last decades concern about bacterial resistance to antibacterial agents because of counter availability, indiscriminate and inappropriate usage of antimicrobial agents has been arised (Neuhauser et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The development of new antibiotics has been accompanied by the steady increase of antibiotic-resistant bacterial strains and the diversity of mechanisms used by bacteria to surpass the lethal effect of these compounds [2]. Many bacterial species show multi-or panresistant phenotypes and most of these multidrug resistant (MDR) bacteria can cause lifethreatening infections, and are of major concerns both in the hospital and the community [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that efflux pumps contribute a varying degree of resistance to antibacterial agents (Costa et al, 2013). The efflux activity has been correlated with increased resistance to antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Further, our data demonstrated that vancomycin+ceftriaxone+VRP1020 combination displayed a 4 fold reduction in MIC which might be due to synergistic activity of vancomycin+ceftriaxone+VRP1020. It has been suggested that efflux pumps belonging to the MFS, particularly NorA and NorB, utilize the proton motive force to energize the transport of antimicrobial compounds across the cell membrane, via an H+: Drug antiport mechanism (Costa et al, 2013;Martins et al, 2009).…”
Section: Discussionmentioning
confidence: 99%